"Fiscal adjustment in Ireland in the 1980s": a comment - Martin, John P. (Economic & Social Studies, 1992)
The Irish experience with fiscal adjustment is interesting, not just for a domestic audience but also for an international one. If one confines the comparison to the OECD countries, the Irish experience can be seen as part of a general trend towards fiscal consolidation, in which it stands out in one major respect. Whether one focuses on 1979 (a cyclical peak in OECD activity) or 1982-83 (the trough of the cycle) as a starting point, Ireland had by 1990 experienced the largest fiscal adjustment of all OECD countries in terms of the size of the swing in the general government budget deficit/GDP ratio. The only other countries to approach it are Japan, Denmark and Sweden.
Keywords: Fiscal policy; Ireland; Tax incidence